Critical evaluation of mock counseling sessions: learning through experience - Rais, Haniza; Hussien, Suhailah (2015)

(untitled)
The development of counseling skills amongst counseling students is an important and one of the primary aims in a counseling program. Effective techniques that are employed would require some exposure for the students to experience the counseling sessions, which include mock counseling sessions. The study, which employed a case study design, focuses on the first stage of the practical exposure, the mock counseling sessions in a lab counseling course, consisted of ten first year counseling students. The course incorporated peer and master coaching to develop students’ skills of questioning in the sessions. Working in pair, students with zero experience in counseling learn the skills by conducting mock sessions, while their fellow classmates observed, then provided feedback and suggested new sets of questions to the pair. All critiques of the sessions were moderated by the instructor. Students were also required to process journal reflections on the activities. The researcher observed the mock sessions and examined students’ process of constructing more meaningful questions in responding to client feedback and meanings reflected. Students’ verbatim on the sharing of their views on the activities in class, where students’ pre and post thoughts on the process of acquiring micro skills were also explored. Data collected were analysed using thematic analysis. The general finding of the study indicate that the mock sessions have provided a positive experience to the first year students. Students were given the opportunities to hear and see different ways of questioning mock client, able to identify their mistakes and reasons for them, and their cognitive skills were challenged to create immediate questions in the mock sessions. Although such sessions have contributed in exposing students to the practical nature of counseling and paving the way for a real counseling setting, students opined that they need more mock sessions due to the limited classroom setting.